Creative capitalism a conversation with Bill Gates, Warren Buffett, and other economic leaders - Banerjee, Abhijit V.; Kinsley, Michael E.; Clarke, Conor 1985- (Simon & Schuster, 2008)
Bill Gates is more than the world's most successful capitalist; he's also the world's biggest philanthropist. Gates has approached philanthropy the same way he revolutionized computer software: with a fierce ambition to change the rules of the game. That's why at the 2008 annual meeting of the World Economic Forum in Davos, Switzerland, Gates advocated a creative capitalism in which big corporations, the distinguishing feature of the modern global economy, integrate doing good into their way of doing business. This controversial new idea is discussed and debated by the more than forty contributors to this book, among them three Nobel laureates and two former U.S. cabinet secretaries. Edited by author and columnist Michael Kinsley, the book started as a first-of-its-kind online conversation that brought together some of the world's best minds to engage Gates's challenge. From Warren Buffett, who seconds Gates's analysis, to Lawrence Summers, who worries about the consequences of multiple corporate objectives, the essays cover a broad spectrum of opinion.--From publisher description.